A promising alternative solvent of perovskite to induce rapid crystallization for high-efficiency photovoltaic devices. Issue 26 (22nd March 2015) - Lv, Minghang; Dong, Xu; Fang, Xiang; Lin, Bencai; Zhang, Shuai; Ding, Jianning; Yuan, Ningyi
<x xml:space="preserve">Abstract</x> The DMAC-based deposition–crystallization method allows control over the dynamics of CH3NH3PbI3 grain growth for the realization of high efficiency devices.